Peningkatan Kapasitas Pelaku UMKM melalui Workshop Penyusunan Proposal Bisnis (Lembaga Pengembangan Kinerja Dosen, 2026)
Limited capacity among micro, small, and medium enterprises (MSMEs) to prepare business proposals and systematically develop business models remains a major challenge in business development and access to financing. This community service program aimed to enhance the capacity of MSMEs fostered by the Bank Indonesia Representative Office of Gorontalo Province in preparing business proposals using the Business Model Canvas (BMC) approach. The program involved 75 MSME participants and was conducted through needs assessment, interactive lectures, workshops, group discussions, presentations, evaluation, and reflection. The training focused on business proposal preparation and the nine elements of the Business Model Canvas, enabling participants to analyze business cases and develop business models collaboratively under facilitator guidance. The results showed a significant improvement in participants' understanding, with the average score increasing from 34.9 in the pre-test to 88.8 in the post-test. Participants also demonstrated improved ability to develop and refine business models systematically. In addition to enhancing knowledge and technical skills, the program promoted collaborative learning, knowledge sharing, and self-confidence. These findings indicate that the Business Model Canvas is an effective tool for supporting structured business planning, while continuous mentoring is recommended to strengthen business proposal development, financial planning, financing access, and business model implementation.